Identificação da fauna parasitária de tartarugas-marinhas encalhadas ao norte do sudoeste atlântico, brasil - Silva, Claudio Giovanio da (2020)
Sea turtles have a cosmopolitan distribution, being represented by only seven species, of which five of them are found in Brazil (Carreta caretta, Chelonia mydas, Eretmochelys imbricata, Lepidochelys olivacea and Dermochelys coriacea) all being listed under some degree of extinction. Several threats have been described affecting the populations of these animals, such as natural aspects of predation, changes in the ecosystem and infectious and parasitic diseases, with the latter being the digenetics, nematodes, hirudins and copepods as the main groups of parasitic agents. Due to the lack of knowledge about the pathogens that affect these animals, the aim of this study was to identify the parasitic fauna of four species of sea turtles (C. mydas, C. caretta, E. imbricata and L. olivacea) from strandings on the coast of the states of Ceará and Rio Grande do Norte during the period from 2010 to 2019. All animals analyzed in this study were found dead in a natural environment or died of complications during the rehabilitation period at the base of the Cetacean Project of Costa Branca. Biometrics and necropsies of the animals were performed for this project. During the necropsy, all organs were analyzed and the collected parasites were fixed in 10% formaldehyde and preserved in 70% alcohol in labeled flasks and sent to the ‘Laboratório de Estudos em Imunologia e Animais Silvestres’. The collected helminths were clarified and stained. Morphometry was analyzed in order to identify parasitic specimens according to identification keys. The parasitic ecological indices of prevalence, average intensity and average abundance were calculated. Nine species belonging to the Digenea subclass, one to the Copepoda subclass, one to the Phylum Nematoda and one to the Hirudinea order were identified. Among the identified species, three of them are reported for the first time on the Brazilian coast, two of which are digenetic (Octangium hyphalum and O. sagitta) and one copepode (Balenophilus manatorum). Another five parasites are reported to occur in new hosts, the digenetics Neoctangium travassosi, Pleurogonius lobatus, Rhytidodes gelatinosus and Deuterobaris proteus and the nematode Sulcascaris sulcata.